An Exploratory Study of Transediting in Students’ Translation Processes - Schrijver, Iris; Van Vaerenbergh, Leona; Van Waes, Luuk (HERMES - Journal of Language and Communication in Business, 2012)
Editing and translating are interconnecting concepts with fuzzy borderlines. In 1989, Stetting coined the term transediting to refer to the overlap of both activities in the translation task. This article reviews the existing literature on this topic. It also reports on an exploratory study of transediting in the translation processes of translation students with different degrees of declarative and procedural knowledge. Four MA translation students were asked to translate an American patient information leaflet (PIL) for a Dutch-speaking audience in accordance with the valid European Medicines Agency (EMA) directive. Of the four participants, two participants possessed only declarative knowledge of both the EMA standards and the text type. The other two participants also had some procedural knowledge, i.e. experience with translating patient information leaflets. Data on the translation processes were collected through think-aloud protocols and computer keystroke logging. By triangulating the data, we found not only a difference in the degree of transediting carried out by the participants, but also divergence in phase allocation of transediting in the translation processes. No clear link could be established between the use of transediting and the participants’ declarative and procedural knowledge.